A novel PI3K/AKT signaling axis mediates Nectin-4-induced gallbladder cancer cell proliferation, metastasis and tumor growth. Issue 1 (28th May 2016) - Zhang, Yijian; Liu, Shibo; Wang, Lei; Wu, Yaoshi; Hao, Jiaqi; Wang, Zheng; Lu, Wei; Wang, Xu-an; Zhang, Fei; Cao, Yang; Liang, Haibin; Li, Huaifeng; et al.
Highlights: The upregulation of Nectin-4 promotes GBC cell proliferation and metastasis. Nectin-4 facilitates GBC progression via PI3K/AKT pathway activation of Rac1. Nectin-4 is potential prognostic factor and therapeutic target in GBC. Abstract: Nectin-4 is a Ca 2+ -independent immunoglobulin-like cell adhesion molecule which has diverse functions in cell–cell adhesion via homophilic and heterophilic interactions. Cell–cell adhesive processes are central to cell polarization, differentiation, proliferation, survival and movement. Here we report that Nectin-4 is substantially overexpressed in gallbladder cancer (GBC), the most common biliary tract malignancy with a high risk of local tumor spread and invasion. Further, Nectin-4 high expression in GBC patients was associated with pathologic T stage and lymph node metastasis status, and the expression level of the downstream target Rac1 and poor prognoses were also correlated with Nectin-4. Ectopic expression of Nectin-4 promoted GBC cell growth, motility and tumor growth in a mouse model. The depletion of Nectin-4 inhibited GBC cell proliferation and migration both in cell culture and in mice. Our data suggest that activation of the PI3K/AKT pathway was involved in the oncogenic function of Nectin-4 to activate Rac1 in GBC. Inhibition of PI3K/AKT with LY294002 and/or Rac1 with NSC23766 impaired Nectin-4-mediated GBC cell proliferation and motility. We hypothesize that Nectin-4 is critical for GBC progression via PI3K/AKT pathway activation of Rac1. Nectin-4 may be a novel prognostic factor and therapeutic target in GBC patients.